CRITERIA AND INDICATORS FOR EVALUATING THE EFFICIENCY OF INNOVATION STRATEGY DEVELOPMENT AND IMPLEMENTATION (Marketing Journal, 2025)
This article examines the criteria and indicators for assessing the effectiveness of developing and implementing an innovation strategy. Also, methods based on multifactor analysis in assessing the prospects for the implementation of an enterprise's strategy and innovative development, the tasks of organizing the business planning process, factors affecting the reduction of material costs in the cost of product production, economic indicators of product quality and other issues are studied in detail.
Keywords: Efficiency assessment; innovation strategy; strategic measures; methods based on multifactor analysis; technological audit; business planning; budgeting system; economic added value; commodity product; recyclable waste . 127